Establishment of a Special Agrarian Court - Bilaleya, Mayariska (CV. Rayyan Dwi Bharata, 2024)
The establishment of a Special Agrarian Court is often the most common problem faced by communities related to land. These problems can be grouped into three categories, namely: uncertainty over land rights, monopoly over land ownership, and the sacrifice of economically weak groups for land tenure interests. One of the reasons why decisions related to land cannot be implemented is because there are several decisions that have permanent legal force but conflict with each other regarding the land object that is being disputed. The purpose of this research is to achieve justice in dealing with agrarian conflict problems, a special institution is needed. who can run the justice mechanism properly. A study has proposed the establishment of an Agrarian Court as a judicial body that focuses on resolving agrarian disputes, with the authority to conduct examinations, trials, and make decisions related to these conflicts. The method used in this research is normative law. The technique applied in this study is juridical. normative that utilizes a legal and conceptual approach.